Safflower as an alternate crop to chickpea under rainfed black soils of Prakasam district of Andhra Pradesh: SAFFLOWER AS AN ALTERNATE CROP TO CHICKPEA UNDER BLACK SOILS OF ANDHRA PRADESH - SAHAJA DEVA; G M V PRASADA RAO; CH VARAPRASADA RAO (Journal of Oilseeds Research, 2019)
Chickpea is a major rabi season crop in Prakasam district of Andhra Pradesh but suffers from moisture stress if there is less (